After Medea, Or What Is in Common between Magic and Translation - Gochev, Georgi (Sledva : NBU Journal of Humanities and Arts, 2020)
A blitz interview with Georgi Gochev, classical scholar and translator, on his recent work on a new Bulgarian version of Euripides’ Medea done especially for Snezhina Petrova’s socially engaged staging of the ancient tragedy.